Strategy of Planning in Absorption of Regional Budget (Study at Regency Government of East Kotawaringin) - Hatta Turachman; Irwan Noor; Mochamad Makmur (Sekolah Pascasarjana Universitas Brawijaya, 2018)
One indication in the absorption of local budget is due to the weakness of planning which resulted in the absorption of the budget is not maximal and concentrated at the end of the budget year. After analyzing the problems in the implementation, then a scenario along with a strategy to be achieved in the planning of acceleration of budget absorption in East Kotawaringin regency to be realized at the beginning of the year and there is no accumulation at the end of the year. The research method used is qualitative descriptive by usingÂ TAIDAÂ (Tracking, Analysing, Imaging, Deciding, Acting)Â method as a tool for conceiving scenarios and strategies to face every possible scenario. Based on the analysis, the most influential and uncertain trend is derived from budget planning and local government commitment. There are four scenarios, namely scenario A, scenario B, scenario C, and scenario D. In order to improve the effectiveness of the program / activity so that the local government finish the program and activities on time with good budget realization level, it is necessary to apply appropriate strategy according to the condition may occur based on a description of the scenario that has been compiled.